2008
DOI: 10.1186/1747-5341-3-24
|View full text |Cite
|
Sign up to set email alerts
|

The 'Brain Drain' of Physicians: Historical antecedents to an ethical debate, c. 1960-79

Abstract: Many western industrialized countries are currently suffering from a crisis in health human resources, one that involves a debate over the recruitment and licensing of foreign-trained doctors and nurses. The intense public policy interest in foreign-trained medical personnel, however, is not new. During the 1960s, western countries revised their immigration policies to focus on highly-trained professionals. During the following decade, hundreds of thousands of health care practitioners migrated from poorer jur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 31 publications
(21 reference statements)
2
52
0
4
Order By: Relevance
“…International migration of healthcare professionals was initially recognized in the 1940s when medical doctors, mainly from Europe, emigrated to the UK (UK) and the USA (US) [1,2]. Common reasons for this migration movement included low wages, limited career opportunities and additional economic factors such as job security and professional development opportunities [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…International migration of healthcare professionals was initially recognized in the 1940s when medical doctors, mainly from Europe, emigrated to the UK (UK) and the USA (US) [1,2]. Common reasons for this migration movement included low wages, limited career opportunities and additional economic factors such as job security and professional development opportunities [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The top two 'source' countries of IMGs in the 1970s-United Kingdom (UK) and Ireland-have been replaced by South Africa and India (5,16,17). Parenthetically, the AIDS epidemic in South Africa has largely been attributed to a severe shortage of physicians due to 'brain drain' to developed countries including Canada and has fuelled global debates about whether it is ethically justified to recruit IMGs from countries which themselves are suffering from acute shortage of trained physicians (13,17,18). Further to this, in-migration of IMGs to Canada (and any other countries) is a multifaceted phenomenon.…”
Section: Pros and Cons: Policy Puzzle And Ethical Concernmentioning
confidence: 99%
“…1 Managing the inherent tension between these competing ethical principles requires leadership and effective health workforce management in both source and destination countries, but also a commitment by the latter to recognise the ethical imperatives of distributive justice (see below) that should not be sacrificed on the altar of expediency. An ethical perspective or lens, pointing to the need for an ethical response to the global inequities in health personnel distribution, was central to the WHO 2006 World Report 8,10 ; and is found in sociological analyses that suggest that recruitment and migration demonstrate that "the uneven global development of capital is at work. " 19 Aluttis et al, 6 discussing the consequences of market approaches, reported that there was an increase from approximately 40 to 270 companies engaged in international nurse recruitment in the United States between the late 1990s and mid-2000s.…”
Section: Analytical Lensesmentioning
confidence: 99%
“…Its consequences for the health systems of source countries became evident in a series of studies on the emigration of doctors from the United Kingdom, mainly to North America, published during the 1960s and 1970s. 8,9 The global scale and consequences of migration, in terms of the maldistribution of health workers, was synthesised in the 2006 World Health Report. 10 This report's statistics are still quoted 11,12 : 36 of the 57 countries with critical shortages are in Africa, which has 25% of the world's burden of disease, but only 3% of health workers worldwide and 1% of global economic resources.…”
Section: Health Workforce Migrationmentioning
confidence: 99%